Use of early non-invasive artificial ventilation in full term newborns with moderate and severe hypoxic ischemic encephalopathy - Klievakina, O. Yu.; Anikin, I. O. (Pathologia, 2020)
The search for and use of alternative respiratory support strategies is promising to improve both close and distant nursing outcomes for newborns with hypoxic ischemic encephalopathy (HIE). Aim. To study the efficacy and safety of early extubation followed by non-invasive lung ventilation in premature infants with severe and moderate hypoxic ischemic encephalopathy. Materials and methods. A prospective, cohortal, randomized study was conducted, which included 60 full term babies. All patients were treated at the intensive care unit for newborns of the Regional Children’s Clinical Hospital in Zaporizhzhia with hypoxic ischemic encephalopathy (HIE) of II and III degree on the Sarnat scale and the presence of respiratory disorders and need for artificial lung ventilation (ALV). The main group included 30 (50 %) patients who in 72 hours after birth were undergoing early tracheal extubation and were transferred to noninvasive nasal lung ventilation with intermittent positive pressure (NIPPV). The comparison group was 30 (50 %) newborns who had a traditional P-SIMV artificial lung ventilation through an intubation tube until they regained consciousness, had no corns and had established a regular pattern of independent breathing. Results. When non-invasive NIPPV ALV was performed, the parameters that corresponded to the parameters of standard endotracheal ventilation were used, while the SpO2 level per day after the NIPPV mode was not significantly changed (P = 0.0765) in comparison with the traditional ALV. Respiratory support duration in patients transferred to NIPPV (P = 0.0004), duration of stay in beds of the intensive care unit (P = 0.0002) and in the in-patient department in general was significantly reduced (P < 0.0001). The total number of pulmonary complications in the main group decreased (P = 0.0487). Conclusions. Early tracheal extubation with subsequent non-invasive ALV can be safely and effectively used in practice to provide respiratory support to newborn infants with HIE. The proposed technique significantly affects the reduction of the total number of complications associated with ALV (P = 0.0375), which in turn reduces the stay of children on hospital beds (P < 0.0001).